Letter from Carl D. Duncan to Patricia Whiting, September 5, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan discusses how Whiting's family is adjusting to the new neighborhood, expresses frustration over the process and limitations of official retirement and comments an the language used in article from Playboy magazine featuring Peter O'Toole.